2009
DOI: 10.1155/2009/146906
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Studies on Transition Metal Complexes of Substituted Derivative of Coumarin‐Part 1

Abstract: The formation constants of binary complexes of d10metal ions Cu(II), Ni(II), Co(II) and Mn(II) with 3-[{3-(3’-chloro phenyl}-prop-2-enoyl]-4-hydroxy-6-methyl-2H-chromen-2-one have been studied by using Irving-Rossoti method at constant temperature 30±1°C and ionic strength μ=0.1 M dM-3was held constant using sodium nitrate as an electrolyte. The factors influencing formation and stabilities of binary complexes have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Ligands bearing oxygen and nitrogen donors play an important role in coordination chemistry where extensive literature is available for the synthesis, structural and biological studies of metal complexes of these ligands [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Apart from conventional donors, heterocyclic compounds played a major role as ligands in metal complexes synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands bearing oxygen and nitrogen donors play an important role in coordination chemistry where extensive literature is available for the synthesis, structural and biological studies of metal complexes of these ligands [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Apart from conventional donors, heterocyclic compounds played a major role as ligands in metal complexes synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, few Schiff bases of coumarin derivatives, identified as potential scaffolds for synthesis of novel biological agents. Therefore, the synthesis of novel Schiff bases from coumarin derivatives and their transition metal complexes remains a main focus of chemical and medicinal research 7,8 . These properties of Schiff bases of coumarin derivatives are due to heterocyclic r ings and substituted functional groups at appropriate positions.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Furthermore, it is reported that such compounds can be used as photo-alignment and photocross-linking units in polymerization processes, [11] laser dyes and nonlinear and optical materials. [12] Also, transition metal complexes especially those with ligands containing chalcone moieties have been the main subject of much research work due to their stability, versatile biological activities [13,14] and potential applications in many fields such as oxidation catalysis and electrochemistry. [15] Metal complexation improves the catalytic activity of chalcones towards oxidation, reduction, hydrolysis and other transformations in organic and inorganic chemistry.…”
Section: Introductionmentioning
confidence: 99%